Head-Mounted Virtual Reality Display: A Feasible Visualization Tool for Minimally Invasive Surgery - Shrestha, Sujan; Mishra, Sushil; Doranga, Sandesh; Shrestha, Shiba; Shrestha, Binod Bade; Ghimire, Pradeep (Journal of Institute of Medicine Nepal, 2025)
Head Mount devices (Virtual Reality platform) can be used as an alternative display device during minimal invasive surgery. Augmentation reality will be the future of navigation guided surgery and virtual reality is the first step towards the future. We report our experience with the use of virtual reality platform in minimal invasive surgery. Head mount device is feasible and replicable approach for better display during minimal invasive surgery and additional augmentation reality will be the next step for navigation-based surgery in future.